The locus coeruleus, a blue spot for early diagnosis and prognosis of Alzheimer’s disease - Farahani, Fatemeh; Anaclet, Christelle; Azizi, Hossein; Gompf, Heinrich S. (Frontiers in Aging Neuroscience, 2025)
Intact functioning of the locus coeruleus-noradrenergic (LC-NA) system is pivotal in the control of numerous central processes, and damage to these systems leads to a wide range of nervous system disorders. The LC, as the main source of noradrenaline (NA) in the mammalian brain, was the first central nervous system (CNS) modulatory structure to be anatomically and biochemically characterized. LC-NA release exerts both excitatory and inhibitory effects on target areas. Over the past few decades, LC damage has been causatively identified as a common factor in CNS diseases, notably neurodegenerative diseases. Moreover, LC damage is the likely manifestation of common pathophysiological processes, thus elevating the LC as a diagnostic and therapeutic target, especially in Parkinson’s and Alzheimer’s diseases (PD & AD). This review also addresses why LC neurons, compared to other areas in particular, are highly vulnerable and sensitive to damage—such as specific anatomical features, tau phosphorylation, and high neuronal energy requirements—will be described in this review article. Finally, we explore whether these known LC vulnerabilities might be leveraged towards improved early diagnostic and prognostic biomarkers for AD.